Photophysical and Electroluminescence Characteristics of Polyfluorene Derivatives with Triphenylamine - Zhang, Qiang; Wang, Po-I.; Ong, Guang Liang; Tan, Shen Hoong; Tan, Zhong Wei; Hii, Yew Han; Wong, Yee Lin; Cheah, Khee Sang; Yap, Seong Ling; Ong, Teng Sian; Tou, Teck Yong; Nee, Chen Hon; et al. (MDPI, 2019)
In this work, polymers of poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-triphenylamine] with side chains containing: pyrene (C1), diphenyl (C2), naphthalene (C3), and isopropyl (C6) structures were synthesized via a Suzuki coupling reaction. The structures were verified using NMR and cyclic voltammetry measurements provide the HOMO and LUMO of the polymers. The polymer with pyrene (C1) and naphthalene (C3) produced photoluminescence in the green while the polymer with the side chain containing diphenyl (C2) and isopropyl (C6) produce dual emission peaks of blue-green photoluminescence (PL). In order to examine the electroluminescence properties of the polymers, the solutions were spin-coated onto patterned ITO anode, dried, and subsequently coated with an Al cathode layer to form pristine single layer polymer LEDs. The results are compared to a standard PFO sample. The electroluminescence spectra resemble the PL spectra for C1 and C3. The devices of C2, C3, and C6 exhibit voltage-dependent EL. An additional red emission peak was detected for C2 and C6, resulting in spectra with peaks at 435 nm, 490 nm, and 625 nm. The effects of the side chains on the spectral characteristics of the polymer are discussed.